Quantitative microbial taxonomy across particle size, depth, and oxygen concentration - Huanca-Valenzuela, Paulina; Fuchsman, Clara A.; Tully, Benjamin J.; Sylvan, Jason B.; Cram, Jacob A. (Frontiers in Microbiology, 2025)
IntroductionMarine particles form in the ocean surface sink through the water column into the deep ocean, sequestering carbon. Microorganisms inhabit and consume carbon in these particles. The East Pacific Rise (EPR) harbors both an Oxygen Deficient Zone (ODZ) and a non-buoyant plume region formed from hydrothermal vents located on the ocean floor, allowing us to explore relationships between microbial community and particle size between a range of environments.MethodsIn this study, we quantified microbial diversity using a fractionation method that separated particles into seven fine scale fractions (0.2–1.2, 1.2–5, 5–20, 20–53, 53–180,180–500, >500 μm), and included a spike-in standard for sequencing the 16S rRNA gene. Size fractionated organic carbon into the same fractions enabled the calculation of bacterial 16S rRNA copies per μg C and per liter.ResultsThere was a large increase in the bacterial 16S rRNA copies/ug C and copies/L on particles >180 μm between the upper water column and the deep water column. Though the total concentration of organic C in particles decreased in the deep water column, the density of bacteria on large particles increased at depth. The microbial community varied statistically significantly as a function of particle size and depth. Quantitative abundance estimates found that ostensibly obligate free-living microbes, such as SAR11 and Thaumarcheota, were more abundant in the free-living fraction but also common and abundant in the particulate size fractions. Conversely, ostensibly obligate particle attached bacteria such as members of Bacteroidetes and Planctomycetes, while most abundant on particles, were also present in the free living fraction. Total bacterial abundance, and the abundance of many taxonomic groups, increased in the ODZ region, particularly in the free-living fraction. Contrastingly, in the non-buoyant plume, there were highly abundant bacteria in the 5–20 and 20–53 μm fractions but reduced bacteria present in the 53–180 and 180–500 μm fractions.ConclusionQuantitative examination of microbial communities highlights the distribution of microbial taxa unburdened by compositional effects. These data are congruent with existing models which suggest high levels of exchange between particle-attached and free-living communities.